2009
DOI: 10.21432/t2fk5s
|View full text |Cite
|
Sign up to set email alerts
|

Comparing students’ perceptions of paper-based and electronic portfolios

Abstract: \Electronic portfolios offer many advantages to their paper-based counterparts, including, but not limited to working on ICT skills, adding multimedia and easier sharing of the portfolio. Previous research showed that the quality of a portfolio does not depend on the medium used. In this article the perceived support for self-reflection of an electronic portfolio and a paper-based portfolio in the same ecological setting are compared. We made use of the fact that during this study about half of the first year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…When the term, "portfolio," is applied for educational purposes, it refers to packages of materials which students or others assemble as a means of communicating their interests and abilities to others (teachers, peers, potential employers, parents, administrators, and others) (van Wesel & Prop, 2008). Portfolios may contain a wide variety of materials and tasks including, but not limited to, photographs, drawings, technical reports, journals, testing results, teacher/student or supervisor/worker conferences, a resume, product or process assessment, check-off sheets, etc.…”
Section: Portfoliosmentioning
confidence: 99%
“…When the term, "portfolio," is applied for educational purposes, it refers to packages of materials which students or others assemble as a means of communicating their interests and abilities to others (teachers, peers, potential employers, parents, administrators, and others) (van Wesel & Prop, 2008). Portfolios may contain a wide variety of materials and tasks including, but not limited to, photographs, drawings, technical reports, journals, testing results, teacher/student or supervisor/worker conferences, a resume, product or process assessment, check-off sheets, etc.…”
Section: Portfoliosmentioning
confidence: 99%
“…Gaitán (2012) pointed out that the clarity of purpose, institutionally or individually, was essential in driving ePortfolio usage. Van Wesel and Prop (2008) found the key factors of successful ePortofolio implementation were self-reflection skills and computer skills. Wuetherick and Dickinson (2015) investigated students' perceptions of ePortfolio use in continuing education environments and results showed that experience and comfort levels with technologies were keys to ePortfolio adoption and continuous implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Van Wesel and Prop (2008) argued that in the past few years, there was a noticeable shift in higher education from the use of paper-based portfolios to electronic portfolios, and that the electronic portfolio became the preferred choice of portfolio in educational settings.…”
Section: Electronic Portfoliosmentioning
confidence: 99%
“…Driessen, Muitjens, van Tartwijk, and van der Vleuten (2007) pointed out that electronic portfolios contain the same content as traditional paper-based portfolios, but they present the information through multimedia technologies and are stored on disks, CDs, Zip disks or file servers on the World Wide Web such as blogs and wikis, which provide several advantages to the traditional portfolios (Avraamidou & Zembal-Saul, 2006;Heath, 2005;van Wesel & Prop, 2008).…”
Section: Electronic Portfoliosmentioning
confidence: 99%
See 1 more Smart Citation